2010
DOI: 10.1038/nature09584
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 controls fasting-induced ketogenesis and its modulation by ageing

Abstract: The multi-component mechanistic target of rapamycin complex 1 (mTORC1) kinase is the central node of a mammalian pathway that coordinates cell growth with the availability of nutrients, energy and growth factors. Progress has been made in the identification of mTORC1 pathway components and in understanding their functions in cells, but there is relatively little known about the role of the pathway in vivo. Specifically, we have little knowledge regarding the role mTOCR1 has in liver physiology. In fasted anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
556
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 568 publications
(589 citation statements)
references
References 28 publications
30
556
1
2
Order By: Relevance
“…1A) and skeletal muscle (Fig. 1B), due to the conflicting previous reports (Sengupta et al ., 2010; Houtkooper et al ., 2011; Leontieva et al ., 2014). In agreement with the results seen by Houtkooper et al ., we observed a 30% decrease in S6 S240/S244 phosphorylation in the livers of Middle‐aged males and females compared to Young (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) and skeletal muscle (Fig. 1B), due to the conflicting previous reports (Sengupta et al ., 2010; Houtkooper et al ., 2011; Leontieva et al ., 2014). In agreement with the results seen by Houtkooper et al ., we observed a 30% decrease in S6 S240/S244 phosphorylation in the livers of Middle‐aged males and females compared to Young (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The question of what happens to mTORC1 signaling during normal aging has therefore received significant attention. As reported in Table 1, numerous studies have reported increased mTORC1 signaling with age in HSCs (hematopoietic stem cells), hypothalamic POMC neurons, and in the liver and lung of mice (Chen et al ., 2009; Sengupta et al ., 2010; Yang et al ., 2012; Leontieva et al ., 2014; Calhoun et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin is considered primarily an mTORC1 inhibitor (Laplante & Sabatini, 2012) but can also inhibit mTORC2. Recent studies distinguish mTORC1 versus mTORC2 effects on lifespan (Selman et al ., 2009) in addition to effects on cell proliferation (Dowling et al ., 2010), metabolism (Sengupta et al ., 2010; Lamming et al ., 2012), protein translation (Thoreen et al ., 2012), immunity (Chi, 2012), and other processes (Yu et al ., 2010; Shimobayashi & Hall, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between CR and health benefits has been empirically demonstrated (Walford, Harris, & Gunion, 1992), the mechanisms underlying this process are multifactorial and still under intensive investigation. Complex association among nutrition‐sensing networks, mammalian target of rapamycin (mTOR; Sengupta, Peterson, Laplante, Oh, & Sabatini, 2010), AMP‐activated protein kinase (AMPK; Canto & Auwerx, 2011), peroxisome proliferator‐activated receptor co‐activator 1α (PGC‐1α; Finley et al., 2012), and sirtuin (Sirt) pathways (Imai, Armstrong, Kaeberlein, & Guarente, 2000) have recently been proposed as possible underlying mechanisms in rodents and nonrodent lower animals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, apart from its role as a metabolic fuel, the effects of 3HB associated with the benefits of CR were reported. The activity of a limiting enzyme of 3HB synthesis, mitochondrial hydroxymethylglutaryl‐CoA synthase (mHMG‐CoAS), is regulated through deacetylation by Sirt3 (Shimazu et al., 2010) and mTOR (Sengupta et al., 2010), master regulators of energy metabolic homeostasis signaling, and these activities have been linked to ameliorating diseases associated with oxidative stress. A more recent finding also showed that 3HB is an endogenous histone diacetyl‐lase inhibitor that helps cells resist oxidative stress (Shimazu et al., 2013).…”
Section: Introductionmentioning
confidence: 99%